2010
DOI: 10.4049/jimmunol.1000536
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Recombinant Calreticulin Fragment 39–272: Implications for Immunobiological Activities of Calreticulin in Health and Disease

Abstract: Although calreticulin (CRT) is a major Ca2+-binding luminal resident protein, it can also appear on the surface of various types of cells and it functions as an immunopotentiating molecule. However, molecular mechanisms underlying the potent immunobiological activity of cell surface CRT are still unclear. In the present study, a recombinant fragment (rCRT/39–272) covering the lectin-like N domain and partial P domain of murine CRT has been expressed in Escherichia coli. The affinity-purified rCRT/39–272 assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(93 citation statements)
references
References 48 publications
8
83
2
Order By: Relevance
“…Furthermore, our result agreed with that of Hong et al (17) who documented that the serum CRT level was significantly higher in their RA patients than the control group. Moreover, the present study revealed statistically significant correlations between the serum CRT levels and CRP (p<0.001), ESR (p=0.002), swollen joints count (p=0.01), tender joints count (p=0.001), and JA-DAS-27 (p=0.001): these results were consistent with the results of Tarr et al (18) who found that CRT levels were positively correlated with ESR, CRP, SJC, and DAS-28 in RA patients.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, our result agreed with that of Hong et al (17) who documented that the serum CRT level was significantly higher in their RA patients than the control group. Moreover, the present study revealed statistically significant correlations between the serum CRT levels and CRP (p<0.001), ESR (p=0.002), swollen joints count (p=0.01), tender joints count (p=0.001), and JA-DAS-27 (p=0.001): these results were consistent with the results of Tarr et al (18) who found that CRT levels were positively correlated with ESR, CRP, SJC, and DAS-28 in RA patients.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, there is a limitation for the detection of sCRT. Another sandwich ELISA system previously reported could only detect sCRT in sera from 23.3% RA patients and 21.9% SLE patients and could not detect sCRT in any of the 48 serum samples from healthy subjects [9]. Thus, new detecting systems for measuring sCRT sensitively need to be developed further.…”
Section: High Expression Level Of Crt In Human Lung Cancer Tissuesmentioning
confidence: 96%
“…Production of mouse mAbs to recombinant CRT/39-272 Complete Freund's adjuvant was mixed with 20 lg of rCRT/39-272 antigen [9]. Female BALB/c mice (6 weeks old) were immunized at day 0 by subcutaneous (s.c.) injection.…”
Section: Samples From Patients and Healthy Subjectsmentioning
confidence: 99%
See 2 more Smart Citations